2020
DOI: 10.1109/access.2020.2967224
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Specific Language Impairment in Children Using Glottal Source Features

Abstract: Developmental dysphasia, also known as specific language impairment (SLI), is a language disorder in children that involves difficulty in speaking and understanding spoken words. Detecting SLI at an early stage is very important for successful speech therapy in children. In this paper, we propose a novel approach based on glottal source features for detecting children with SLI using the speech signal. The proposed method utilizes time-and frequency-domain glottal parameters, which are extracted from the voice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 24 publications
2
15
0
1
Order By: Relevance
“…Previous studies [ 85 91 ] had demonstrated that speech can be viewed as a symbol of diagnosing SLI. In [ 85 – 87 ], 1582 acoustic features were extracted from 34 low-level descriptors and its 21 statistical functionals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies [ 85 91 ] had demonstrated that speech can be viewed as a symbol of diagnosing SLI. In [ 85 – 87 ], 1582 acoustic features were extracted from 34 low-level descriptors and its 21 statistical functionals.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, some methods were proposed for speaker-independent classification in [ 90 , 91 ]. The top-20 LPC features were selected from 408 LPCs using Mann–Whitney U test and Spearman’s correlation in [ 90 ], which achieved an accuracy of 97.90% on the SLI detection task.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies [92,93,94,95,96,97,98] had demonstrated that speech can be viewed as a symbol of diagnosing SLI. In [92,93,94], 1582 acoustic features were extracted from 34 low-level descriptors and its 21 statistical functionals.…”
Section: Network Visualization Using Grad-cammentioning
confidence: 99%
“…In contrast, some methods were proposed for speaker-independent classification in [97,98]. The top-20 LPC features were selected from 408 LPCs using Mann-Whitney U-test and Spearman's correlation in [97], and it achieved an accuracy of 97.90% on the SLI detection task.…”
Section: Network Visualization Using Grad-cammentioning
confidence: 99%
See 1 more Smart Citation